Weak Comparison Principle for Weighted Fractional p-Laplacian Equation. (21st December 2020) - Xie, Jin
Abstract : The aim of this paper is to establish a weak comparison principle for a class fractional p -Laplacian equation with weight. The nonlinear term f x, s > 0 is a Carathéodory function which is possibly unbounded both at the origin and at infinity and such that f x, s s 1 − p decreases with respect to s for a.e. x ∈ Ω .